2015
DOI: 10.1002/oby.21258
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal perfluoroalkyl substance exposure and child adiposity at 8 years of age: The HOME study

Abstract: ObjectiveTo examine relationships between prenatal perfluoroalkyl substance (PFAS) exposure and adiposity in children born to women who lived downstream from a fluoropolymer manufacturing plant.MethodsData are from a prospective cohort in Cincinnati, OH (HOME Study). We measured perfluorooctanoic (PFOA), perfluorooctane sulfonic (PFOS), perfluorononanoic (PFNA), and perfluorohexane sulfonic (PFHxS) acids in prenatal serum samples. We estimated differences in body mass index z-scores (BMI), waist circumference,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

15
159
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 201 publications
(176 citation statements)
references
References 38 publications
15
159
2
Order By: Relevance
“…High PFOS exposure was associated with a higher and steeper postload glucose trajectory, a greater tendency toward glucose intolerance, and a 3.4 times higher prevalence of diabetes, whereas an opposite relationship was found for other congeners of PFASs (PFOA, perfluorononanoic acid, and perfluoroundecanoic acid) (25). Previously published longitudinal studies (12)(13)(14)26,27) have relied on prenatal or perinatal exposure; however, long elimination half-lives of the substances from the human organism pave the way for using childhood PFAS exposure as a proxy for prenatal and postnatal exposure. Previous studies (12)(13)(14) have indicated that exposure to different congeners of PFASs in utero may cause permanent physiological changes, predisposing subjects to later weight gain.…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…High PFOS exposure was associated with a higher and steeper postload glucose trajectory, a greater tendency toward glucose intolerance, and a 3.4 times higher prevalence of diabetes, whereas an opposite relationship was found for other congeners of PFASs (PFOA, perfluorononanoic acid, and perfluoroundecanoic acid) (25). Previously published longitudinal studies (12)(13)(14)26,27) have relied on prenatal or perinatal exposure; however, long elimination half-lives of the substances from the human organism pave the way for using childhood PFAS exposure as a proxy for prenatal and postnatal exposure. Previous studies (12)(13)(14) have indicated that exposure to different congeners of PFASs in utero may cause permanent physiological changes, predisposing subjects to later weight gain.…”
Section: Discussionmentioning
confidence: 91%
“…Previously published longitudinal studies (12)(13)(14)26,27) have relied on prenatal or perinatal exposure; however, long elimination half-lives of the substances from the human organism pave the way for using childhood PFAS exposure as a proxy for prenatal and postnatal exposure. Previous studies (12)(13)(14) have indicated that exposure to different congeners of PFASs in utero may cause permanent physiological changes, predisposing subjects to later weight gain. However, other longitudinal studies have not found any relationship between prenatal exposure and anthropometry at 7 years of age (26) or early life exposure and risk of overweight and obesity in adulthood (27).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…No associations were observed for the other PFCs measured (PFOS, PFHxS and PFNA). The investigators noted that their study was limited by the use of less-refined measures of body fatness and that future studies should take advantage of more comprehensive measures such as DXA (32).…”
Section: Discussionmentioning
confidence: 99%